Chlorella virus pyrimidine dimer glycosylase and Escherichia coli endonucleases IV and V have incision activity on 2, 2, 4-triamino-5(2H)-oxazolone. (December 2015) - Kino, Katsuhito; Suzuki, Masayo; Morikawa, Masayuki; Kobayashi, Takanobu; Iwai, Shigenori; Miyazawa, Hiroshi
Abstract Introduction 2, 2, 4-Triamino-5(2H )-oxazolone (Oz) in a DNA strand is an oxidation product of guanine and 8-oxo-7, 8-dihydroguanine, and such a lesion can cause G-to-C transversions. Previously, Fpg/Nei and Nth were shown to have incision activity on Oz. Findings We investigated the activities of chlorella virus pyrimidine dimer glycosylase (cvPDG) andEscherichia coli endonucleases IV (Nfo) and V (Nfi) on Oz. Although the three enzymes have different repair mechanisms from Fpg/Nei and Nth, they still had incision activity on Oz. Conclusions Given the incision activities of cvPDG, Nfo and Nfi on Oz in addition to Fpg/Nei and Nth, Oz is DNA damage that can be repaired by diverse enzymes.